17β-Estradiol Promotes Trained Immunity in Females Against Sepsis via Regulating Nucleus Translocation of RelB - Sun, Zhiheng; Pan, Yuchen; Qu, Junxing; Xu, Yujun; Dou, Huan; Hou, Yayi (Frontiers in Immunology, 2020)
Sepsis is more common among males than females, and the unequal estrogen levels have been suspected to play a vital role in gender differences. Recently, trained immunity is reported to be a novel strategy for the innate immune system to fight infection. However, it has not been clarified whether β-glucan-induced trained immunity causes different responses to early sepsis between male and female mice. In this study, sepsis was induced in mice by intraperitoneal injection of Escherichia coli (E. coli). The changes of inflammatory cytokines expression, and macrophage polarization in male, female, and ovariectomized C57BL/6 mice in sepsis model were investigated. For in vitro studies, different macrophages were treated with LPS. The function of estradiol (E2) on macrophage cell lines was verified and the mechanism of E2 affecting trained immunity was explored. We demonstrated that β-glucan-induced trained immunity was more resistant to sepsis in female than male mice. Macrophage polarization toward the M1 phenotype, which exhibited enhanced trained immunity, was related to the difference in sepsis resistance between female and male mice. Moreover, ovariectomized (OVX) mice manifested serious sepsis consequences with a weaker trained immunity effect than female mice. Female bone marrow-derived macrophages (BMDMs) were also apt to be polarized to the M1 phenotype in response to trained immunity in vitro. Furthermore, E2 promoted trained immunity in macrophage cell lines J774 and RAW264.7. E2 was also verified to facilitate trained immunity in primary BMDMs from female and male mice. Mechanistically, we found that E2 inhibited the nuclear translocation of RelB, which is a member of non-canonical pathway of NFκB and contributes to macrophage polarization to change the intensity of trained immunity. This study is the first to indicate the role of E2 in the trained immunity induced by β-glucan to protect against E. coli-induced sepsis via the non-canonical NFκB pathway. These results improve our understanding of the molecular mechanisms governing trained immunity in gender differences.